Pengaruh Kualitas Produk dan Citra Merek terhadap Keputusan Pembelian Handphone Oppo pada Toko Max-Indo di Kota Padang - Maria Magdalena; Wilzarwan Wilzarwan (JURNAL PUNDI, 2019)
ABSTRACT            For the purpose of this study namely, to analyze the effect  of product quality, and brand image, on the purchasing decisions of the oppo brand handphone at the Max-Indo Padang shop. The population in this study is, all consumers who had bought the oppo brand mobile in the Max-Indo store in Padang City. Which numbered 1,836 people, while for the study sample were 100 respondents. The sample technique  used is, purposive sampling method by taking samples based on certain criteria. Data analysis techniques used to test hypotheses are multiple linear regression and statistical test T. The result of the study show that the product quality variable has a significance value of 0.034 and the brand image has a significance influence of 0.000. then the product quality, and brand image variables have a significant influence on the purchase decisions of the Oppo brand mobile phone at the Max-indo Padang shop. Keyword : Product Quality, Brand Image, and Purchasing Decision.